The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2nr03809a
|View full text |Cite
|
Sign up to set email alerts
|

In situTEM observations of growth mechanisms of PbO nanoparticles from a Sm-doped PMN-PT matrix

Abstract: An excess PbO is usually added in the raw materials to compensate PbO volatilization during high-temperature sintering (1-x)Pb(Mg1/3Nb2/3)O3-xPbTiO3 (PMN-PT) piezoelectric material. However, the detailed growth mechanism of liquid phase and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…In the BiOCl region, the two crystal planes had lattice spacings of 0.251 and 0.273 nm, corresponding to the (003) and (110) planes, respectively. 28,29 Therefore, the SEM, TEM, and HRTEM results confirmed the successful synthesis of the Bi 5 Ti 3 FeO 15 / BiOCl heterostructure. Figure 2f were obtained at the applied voltage of ±8 V, indicating that Bi 5 Ti 3 FeO 15 /BiOCl (4 h) had good piezoelectricity.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…In the BiOCl region, the two crystal planes had lattice spacings of 0.251 and 0.273 nm, corresponding to the (003) and (110) planes, respectively. 28,29 Therefore, the SEM, TEM, and HRTEM results confirmed the successful synthesis of the Bi 5 Ti 3 FeO 15 / BiOCl heterostructure. Figure 2f were obtained at the applied voltage of ±8 V, indicating that Bi 5 Ti 3 FeO 15 /BiOCl (4 h) had good piezoelectricity.…”
Section: Resultsmentioning
confidence: 52%
“…In the Bi 5 Ti 3 FeO 15 region, the crystal plane with a lattice spacing of 0.262 nm belonged to the (024) plane. In the BiOCl region, the two crystal planes had lattice spacings of 0.251 and 0.273 nm, corresponding to the (003) and (110) planes, respectively. , Therefore, the SEM, TEM, and HRTEM results confirmed the successful synthesis of the Bi 5 Ti 3 FeO 15 /BiOCl heterostructure. Figure f displays the piezoelectric property of Bi 5 Ti 3 FeO 15 /BiOCl (4 h) measured with piezoresponse force microscopy (PFM).…”
Section: Resultsmentioning
confidence: 64%
“…Sharp diffraction spots indicate that these nanoparticles are single crystalline and well crystallized. Figure f shows the corresponding high-resolution TEM (HRTEM) image, confirming that Fe 2 O 3 nanoparticles are well crystallized. , The lattice spacings of the marked two crystal planes are 0.285 and 0.287 nm, corresponding to (21̅0) and (110) of Fe 2 O 3 , respectively.…”
Section: Results and Discussionmentioning
confidence: 71%
“…Figure 2f shows the corresponding high-resolution TEM (HRTEM) image, confirming that Fe 2 O 3 nanoparticles are well crystallized. 41,42 The lattice spacings of the marked two crystal planes 43,44 In Figure 3c, it is shown that the two peaks at 530.15 and 531.4 eV are lattice oxygen and chemisorbed oxygen, respectively. 45 The tribocatalytic activity of Fe 2 O 3 was first evaluated by the degradation of RhB using magnetic stirring with different speeds using a polytetrafluoroethylene (PTFE) magnetic stirring rod (A-type).…”
Section: Resultsmentioning
confidence: 99%